(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Oncological diseases require expensive diagnostic procedures, their therapy captures a lot of time and effort, in addition, patients, as well as the principle , have a need for hospitalization. Among the inhabitants of Western countries, lung, skin, gastrointestinal tract cancer, as well as prostate cancer, have become the most widespread.The possibility of cancer of various etiologies during its own existence is shown in the figure. Almost all the years, the main methods of treating cancer were microsurgery, as well as therapy. Recognition of the original source is of great importance, so this is often considered a key diagnostic aspect of the direction of the disease. In this case, after all, the period of local metastases significantly complicate the difficult procedure, and also, being not noticed in a timely manner, have every chance of being a factor in the lethal outcome. propensity as well as proof of the ability to form a malignant neoplasm together with the greatest possibility.